FAKTOR-FAKTOR YANG MEMPENGARUHI PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA USAHA BARBERSHOP - Niken Kusumawardani (Jurnal Akuntansi dan Keuangan (JAK), 2019)
This research aims to; 1) Determine the effect of education level on the preparation of SAK ETAP financial statements; 2) Determine the influence of educational background on the preparation of SAK ETAP financial statements; 3) Determine the effect of business scale on the preparation of SAK ETAP financial statements; 4) Determine the effect of business experience on the preparation of SAK ETAP financial statements. The sample of this research is the Barbershop Micro, Small and Medium Enterprises (UMKM) in Tanjung Senang District. This sampling method uses random sampling. Data were analyzed using multiple linear regression analysis. The results showed that the level of education, educational background, and business scale did not significantly influence the preparation of SAK ETAP financial statements. Only business experience has a significant effect on the preparation of SAK ETAP financial statements.